2021
DOI: 10.1002/lsm.23503
|View full text |Cite
|
Sign up to set email alerts
|

Stone ablation rates using innovative pulse modulation technology: Vapor tunnel, virtual basket, and bubble blast. An in vitro experimental study

Abstract: Introduction and Objectives: Virtual Basket TM , Bubble Blast TM , and Vapor Tunnel TM are three laser pulse modulation technologies that modify the holmium: yttrium-aluminum-garnet (Ho:YAG) laser pulse transmission through the creation of bubbles emerging from the fiber tip with different effects on the target stone. The primary outcome of the current study was to test the stone ablation rates for the different pulse modulation modes, Virtual Basket, Bubble Blast, and Vapor Tunnel, using different power, ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In addition, the influence of pulse modulation modes, such as MM and VBM, on irrigation temperatures has also been investigated. Both the MM and VBM are two-staged laser shot modes based on Moses technology and available by using Pulse 120H and Cyber Ho 100W, respectively [ 11 , 12 ]. In these modes, the second laser pulse penetrates the bubble of the first laser pulse.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the influence of pulse modulation modes, such as MM and VBM, on irrigation temperatures has also been investigated. Both the MM and VBM are two-staged laser shot modes based on Moses technology and available by using Pulse 120H and Cyber Ho 100W, respectively [ 11 , 12 ]. In these modes, the second laser pulse penetrates the bubble of the first laser pulse.…”
Section: Discussionmentioning
confidence: 99%
“…The future of lithotripsy research is focused on either optimizing current laser settings or developing new laser technology altogether. In a study comparing several laser pulse modulation technologies from Quanta Systems, the Virtual Basket demonstrated improved ablation rates by creating bubbles from the fiber tip compared to either Bubble Blast or Vapor Tunnel [ 26 ]. A comparison of holmium software systems from either Lumenis with Moses or Quanta Systems with Virtual Basket has not been explored but would be valuable to explore in the future.…”
Section: Discussionmentioning
confidence: 99%
“…MT has shown in multiples in-vitro studies superiority to short pulse and regular pulse [21,22]. Virtual Basket have shown to be better than Vapor tunnel and bubble blast at HP [19]. For now, only one in vitro study has shown better ablation with MT at distance mode vs. long pulse [23] and one in-vitro study has reported that Virtual Basket is better than long pulse achieving less operative time, better stone free rate and lower retropulsion [24 ▪ ] although more clinical evaluations are missing as some studies have also reported similar efficiency compared to long pulse [16 ▪ ].…”
Section: Holmium:yagmentioning
confidence: 99%